1998
DOI: 10.1103/physrevb.58.7434
|View full text |Cite
|
Sign up to set email alerts
|

Wave-vector-dependent exchange splitting in a local moment system

Abstract: The electronic structure of strained thin films of Gd has been studied with spin-and angle-resolved photoemission and spin-polarized inverse photoemission. The spin-dependent electronic structure is dominated by a very distinct k dependence of the exchange splitting. The surface magnetic structure is observed to be different from that of the bulk, as indicated by the different electronic structure and a much higher surface Curie temperature. The 4% strain within the Gd films results in an enhanced Curie temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 69 publications
(89 reference statements)
3
46
0
Order By: Relevance
“…The IPES system, with a resolution of 420 meV, incorporates an Erdman-Zipf electron gun [23] along with a Geiger-Müller detector with a SrF 2 window in an apparatus previously described elsewhere [24]. The electron energy was swept from 5.5 to 12.5 eV, at incident angles between normal and 60 degrees, or from zone center (Γ ) out to the Brillouin zone edge (Χ ).…”
Section: Methodsmentioning
confidence: 99%
“…The IPES system, with a resolution of 420 meV, incorporates an Erdman-Zipf electron gun [23] along with a Geiger-Müller detector with a SrF 2 window in an apparatus previously described elsewhere [24]. The electron energy was swept from 5.5 to 12.5 eV, at incident angles between normal and 60 degrees, or from zone center (Γ ) out to the Brillouin zone edge (Χ ).…”
Section: Methodsmentioning
confidence: 99%
“…With this aim, we perform a detailed comparison of theoretical surface and bulk band structures, with experimental data obtained by spin-polarized photoemission ͑SPES͒ and spin-polarized inverse photoemission ͑SPIPES͒ ͑partly published elsewhere 8,29 ͒. The band structures have been calculated by the linear augmented-plane-wave ͑LAPW͒ method for thin films.…”
Section: Introductionmentioning
confidence: 99%
“…21 The expansive 4% in-plane strained Gd͑0001͒ on Mo͑112͒ results in a quite different electronic structure and altered magnetic properties compared to the strain relieved Gd͑0001͒ grown on W͑110͒, 27 as noted elsewhere. 8,21,28,29 Based on studies of rare-earth alloys, Andrianov 19,20 suggested that the Fermi surface is sensitive to both composition and lattice deformation. It was shown 28 that the relief of the strain in Gd͑0001͒ on Mo͑112͒ with increasing film thickness results in a spin-polarized electronic structure that is increasingly similar to the largely unstrained Gd͑0001͒ films grown on W͑110͒.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations